Growth and development of children living in incarceration environments of the province of Buenos Aires, Argentina - Di Iorio, Susana (Revista Española de Sanidad Penitenciaria.)
Objective: The objective of this study was to examine the nutritional status, psychomotor and socioemotional development of children living with their mothers in prison in the province of Buenos Aires, Argentina.Material and method: Sex, age, weight and height were measured in children (37) residing with their mothers (28) in Prison No. 33 of the SPB. Nutritional indicators were calculated and analyzed according to the WHO international reference (2006). National Research Test (PRUNAPE) and the parental questionnaire Ages and Stages Questionnaires: Socio-Emotional®, Second Edition (ASQ:SE-2) were applied to evaluate development.Results: Anthropometric evaluation showed that 7 of children under 2 years presented low weight, 3 alert of low weight, 28 high weight and 14 low height. Children over 2 years of age showed 37.5 of high weight and 25 of risk of overweight. There were no children with short stature. PRUNAPE and ASQ:SE-2 tests: in the 30 cases that completed both tests more than half (53.3) obtained scores within the expected range. In the group of children with both tests who did not pass the PRUNAPE (n = 9), the result found in the ASQ-SE 2 was diverse: 66.6 within expectations and 33.3 at risk. Neither of children with both tests who did not pass the ASQ:SE-2 passed the PRUNAPE.Conclussion: There were high prevalences of excess weight and high percentages of risk in psychomotor development, considerably higher than in the general population. There is a need to take action to reduce the harmful effect of childhood confinement.